2007
DOI: 10.1016/j.wocn.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Guttural vowels and guttural co-articulation in Ju∣’hoansi

Abstract: Ju|'hoansi contains parallel glottalization, breathiness and epiglottalization on consonants and vowels, as well as uvularization on consonants. There are voice quality cues associated with epiglottalized vowels that parallel those found with breathy and glottalized vowels. There is also guttural coarticulation, whereby aspirated, glottalized, uvularized and epiglottalized consonants spread acoustic voice quality cues onto a following vowel. The laryngeal coarticulation exhibited by click consonants is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Because the phonation contrast is strongest in the first third of vowels, the analyses that follow are limited to that time interval. However, the results for CPP are in keeping with Miller (2007), who found that Harmonics-to-noise ratios can capture the acoustic SIMILARITY of non-modal phonation types, rather than their differences. Linear mixed-effects models were run to determine the main effects and interactions of various predictors like phonation, sex, tone, and aspiration on the four acoustic measures.…”
Section: Timecourse During Vowelssupporting
confidence: 86%
See 3 more Smart Citations
“…Because the phonation contrast is strongest in the first third of vowels, the analyses that follow are limited to that time interval. However, the results for CPP are in keeping with Miller (2007), who found that Harmonics-to-noise ratios can capture the acoustic SIMILARITY of non-modal phonation types, rather than their differences. Linear mixed-effects models were run to determine the main effects and interactions of various predictors like phonation, sex, tone, and aspiration on the four acoustic measures.…”
Section: Timecourse During Vowelssupporting
confidence: 86%
“…in Gobl & N ⁄ ı Chasaide 1999), English (Löfqvist & McGowan 1992, Garellek 2010, White Hmong (Garellek 2010), Korean (Cho, Jun & Ladefoged 2002, Garellek 2010, Navajo, Tagalog (Blankenship 1997), and Ju|'hoansi (Miller-Ockhuizen 2003, Miller 2007. Such laryngeal coarticulation has been shown in a number of languages, including Swedish, French, German, Italian (e.g.…”
Section: Aspirated Onsetsmentioning
confidence: 96%
See 2 more Smart Citations
“…Traill [1986] claimed that the so-called sphincteric phonation in !Xóõ is produced by vibration of the epilaryngeal structures; similarly, the 'raucous' and 'deep' pharyngeals of Agul [Catford, 1983, p. 347] probably involve epilaryngeal vibration, as Esling [1999, p. 364] suggests. Miller [2007] and Miller et al [2009] posit an AE phonatory mechanism for distinctive 'epiglottalized' vowels in Ju|'hoansi and N|uu. The vocal style of the Jing role in Chinese Opera ostensibly epilaryngeal vibration, which would account for its growled quality [Tsai et al, 2010].…”
mentioning
confidence: 99%